„Zētei historian exaision”. Historycy bizantyńscy w dialogu ze swoimi źródłami - Kompa, Andrzej (Przegląd Nauk Historycznych, 2014)
The text explores the multifaceted relations between the Byzantine historians and the sources they used. Authorial, subjective role of the modern historian is underlined as the preserved bulk for the Byzantine literary output reveals much specificity, misleading clues as opportunities for diverse interpretation. In consequence, a need for multidiciplinary attitude and cautious source criticism seems even more important than elsewhere. The complexe interactions between the Byzantine authors and their predecessors are at the core of the issue. Thus, not only standard verification of authenticity and reliability of the passages, but also a search for mentality of the authors, rationale and incentives of their literary activity, intellectual categories, and self-evaluation of the ancient and medieval authors demands gathering and using of wide variety of sources to compare. Such material is (or should be) drawn from as wide as possible range of the sources, including disciplines that stemmed from reasons in a priori opposition to historiography sensu stricto. Problem of source-in-source is shown through examples, such as passages from Scriptores Historiae Augustae or the chronographical duo, i.e. George Syncellus and Theophanes the Confessor. Other cases of problematic share of authorship follow; some oeuvres functioned permanently as in constant working process even long after their basic completion – one should not overlook a statement of patriarch Photius on John Moschus, who claimed that none of the extant copies of his Spiritual Meadow shared the numer of stories that constituted it. Despite the ordinary borrowings from the previous authors, the Byzantine authors are to be treated individually, as their individualism breaks through the barriers of topoi, casual narrative concepts or their emulative attitudes. As for the historians of all sorts, the tiny remark of an unknown copyist, compiler or author, inscribed into a patriographic, Constantinopolitan piece – Zētei historian exaision (Check out this unbelievable story) – may be treated as a symbol of their basic criticism and inquisitiveness, even if the possibilities of verification were mediocre, rationalism distorted, and the methods – insufficient.